Integridade dos dados meteorológicos obtidos por duas estações meteorológicas automatizadas - Oliveira, Paulo José Desiderio de [UNESP] (2014)
The estimation of reference evapotranspiration (ETo) is used both for planning and for irrigation management. Meteorological data of dubious quality, obtained from automatic weather stations to estimate ETo, can lead to improper irrigation management. The purpose of this study was to evaluate the integrity of data from two automatic weather stations to estimate ETo. The meteorological data were evaluated for the following variables: solar radiation, air temperature, air humidity, wind speed and rainfall. The stations are installed in FCAV / UNESP, Jaboticabal, SP. Techniques that verify the integrity of weather data for estimating ETo, and according to this criteria, the data relative humidity and wind speed of the two stations were applied were not acceptable. The analysis leads to the conclusion that, in the studied stations, we recommend doubling the sensors for air temperature and relative humidity, wind speed and precipitation